Primary versus Staged Closure of Exomphalos Major: Cardiac Anomalies Do Not Affect Outcome - Rees, Clare M.; Tullie, Lucinda; Pierro, Agostino; Kiely, Edward; Curry, Joe I.; Cross, Kate; Yates, Robert; Eaton, Simon; De Coppi, Paolo (European Journal of Pediatric Surgery, 2018)
Aim The objective of the study is to describe management of exomphalos major and investigate the effect of congenital cardiac anomalies.Methods A single-center retrospective review (with audit approval) was performed of neonates with exomphalos major (fascial defect ≥ 5cm ± liver herniation) between 2004 and 2014.Demographic and operative data were collected and outcomes compared between infants who had primary or staged closure. Data, median (range), were analyzed appropriately.Results A total of 22 patients were included, 20 with liver herniation and 1 with pentalogy of Cantrell. Gestational age was 38 (30–40) weeks, birth weight 2.7 (1.4–4.6) kg, and 13 (60%) were male. Two were managed conservatively due to severe comorbidities, 5 underwent primary closure, and 15 had application of Prolene (Ethicon Inc) mesh silo and serial reduction. Five died, including two managed conservatively, none primarily of the exomphalos. Survivors were followed up for 38 months (2–71). Cardiac anomalies were present in 20 (91%) patients: 8 had minor and 12 major anomalies. Twelve (55%) patients had other anomalies. Primary closure was associated with shorter length of stay (13 vs. 85 days, p = 0.02), but infants had similar lengths of intensive care stay, duration of parenteral feeds, and time to full feeds. Infants with cardiac anomalies had shorter times to full closure (28 vs. 62 days, p = 0.03), but other outcomes were similar.Conclusion Infants whose defect can be closed primarily have a shorter length of stay, but other outcomes are similar. Infants with more significant abdominovisceral disproportion are managed with staged closure; the presence of major cardiac anomalies does not affect surgical outcome.
Keywords: exomphalos major; surgical outcome; abdominal wall defect; congenital cardiac defect; silo